2017
DOI: 10.3390/plants6040044
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Constituents and Antifungal Activity of Ficus hirta Vahl. Fruits

Abstract: Phytochemical investigation of Ficus hirta Vahl. (Moraceae) fruits led to isolate two carboline alkaloids (1 and 2), five sesquiterpenoids/norsesquiterpenoids (3–7), three flavonoids (8–10), and one phenylpropane-1,2-diol (11). Their structures were elucidated by the analysis of their 1D and 2D NMR, and HR-ESI-MS data. All of the isolates were isolated from this species for the first time, while compounds 2, 4–6, and 8–11 were firstly reported from the genus Ficus. Antifungal assay revealed that compound 8 (na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 19 publications
1
39
0
Order By: Relevance
“…, and eriodictyol-7-O-β-d-glucoside were isolated and identified by nuclear magnetic resonance (NMR) and high resolution electrospray ionization mass spectrometry (HR-ESI-MS), as previously described [8,11].…”
Section: Collection Of Plant Materials and Reagentsmentioning
confidence: 99%
See 2 more Smart Citations
“…, and eriodictyol-7-O-β-d-glucoside were isolated and identified by nuclear magnetic resonance (NMR) and high resolution electrospray ionization mass spectrometry (HR-ESI-MS), as previously described [8,11].…”
Section: Collection Of Plant Materials and Reagentsmentioning
confidence: 99%
“…Certain studies regarding the chemical composition and pharmacological activities of F. hirta Vahl. reported that benzene derivatives, phenolics, and glycosides of flavonoid are majorly present in this plant [2,5,11,12]. Recently, three new monosubstituted benzene derivatives elucidated as (2R) methyl 2-O-β-d-glucopyranosyl-2-phenyl acetate, (2S) 2-O-benzoyl-butanedioic acid-4-methyl ester, and 4-O-benzoyl-quinic acid were initially isolated from the ethanolic extracts of HFF by our group members [8], and one new compound depicted a potent antifungal effect against Penicillium italicum isolated from citrus fruits.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…PiCB (CAS-No. 75829-43-5, Figure 1) was isolated and purified from air-dried powder of hairy fig fruits (HFF) [14] by extraction applying an ultrasonic-associated method with 95% ethanol at reflux in the Jiangxi key laboratory for postharvest technology and nondestructive testing of fruits and vegetables at Jiangxi Agricultural University (Nanchang, China). The ethanol solution was evaporated under reduced pressure at 45 • C to recover the ethanol solvent.…”
Section: Isolation and Purification Of Pinocembroside (Picb)mentioning
confidence: 99%
“…Moreover, the fruits of hairy fig are a famous herb used by Hakka people in Chinese folk medicine for inhibiting tumor growth, promoting lactation, as anticoagulant, and for improving fatigue resistance [18,19]. Currently, our previous research demonstrated that HFE has strong antifungal activity against P. italicum and P. digitatum in vitro conditions [20,21]. Not surprisingly, chitosan coating enriched with HFE provided an enhanced antifungal activity, and it is likely that research will broaden the practicability of the botanical fungicide.…”
Section: Introductionmentioning
confidence: 99%